IMPLEMENTASI PENDIDIKAN KARAKTER PADA PROFIL PELAJAR PANCASILA BAGI GURU SD PRANTAAN BOGOREJO - haryanti, Dwi; Gita Permatasari, Kristina (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2023)
This community service activity was motivated by the lack of optimal strengthening of character education through the Pancasila student profile for teachers in the field. The objectives of this community service activity are to; 1) strengthen character and competence, 2) actively participate in planning active and continuous learning, 3) develop skills, attitudes and knowledge, 4) solve problems in various learning situations, 5) be responsible and care for the surrounding situation and 6) value learning so as to achieve educational goals. Based on the training that has been carried out at SD Prantaan Bogorejo, this service activity received a positive response from the teachers who participated in the activity. This can be seen from the high enthusiasm of the teachers when participating in this training activity. The main thing that was done during the implementation of this service activity was that teachers who were training participants were asked to identify a problem related to character education through the Pancasila student profile. Then teachers are given an understanding of the materials and problems related to strengthening character education. As feedback from this activity, the Education Coordinator and elementary school teachers said that they were willing to become target schools for various activities to improve the quality of education in their schools. It is hoped that from the Education Coordinator of Bogorejo District and teachers in elementary schools, their school achievements can continue to increase with the collaboration built with Padang State University.Keywords: Character Education, Pancasila Learner, Teacher